CYDIA Award 2026 Impact Category - Krambia-Kapardis, Maria (My University, 2026)
CYDIA Awards® 2026 | Impact | Dr. Maria Krambia-Kapardis This award honours those advancing change through responsible business, innovation and community engagement, creating lasting positive impact.
Keywords: Business and industry